Key to exercises in CGE modeling using GAMS - Lofgren, Hans (International Food Policy Research Institute, 2000)
This easy-to-use manual presents exercises related to computable general equilibrium (CGE) models, which represent one type of economywide model used in policy analysis. This type of model explicitly recognizes that changes affecting one part of the economy can have repercussions throughout the rest of the economy. They are particularly useful in capturing the indirect effects of a policy change. This manual is designed to help the reader construct, modify, and conduct food policy simulations using GAMS (General Algebraic Modeling System), one of the most popular softwares for solving CGE models. The model that is developed in the concluding exercise provides a starting point for applied policy analysis. A supplement to the manual provides the keys to the exercises. The manual also comes with a CD-ROM with a limited-capacity version of GAMS and a diskette with help files.